2007
DOI: 10.1007/s00432-007-0191-3
|View full text |Cite
|
Sign up to set email alerts
|

Diminished quality of life in patients with cancer correlates with tryptophan degradation

Abstract: Results suggest that immune-mediated tryptophan degradation may contribute to cancer-induced QoL deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 34 publications
3
46
0
Order By: Relevance
“…In line with previous reports using plasma CRP levels and ESR to evaluate the association between the kynurenine pathway and inflammation, we found a strong relation between these inflammatory markers and parameters for TRP oxidation [27,28,36]. The correlation between the KYN/TRP ratio and the NLR, which is an index of systemic inflammatory response [37], additionally strengthens this association.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In line with previous reports using plasma CRP levels and ESR to evaluate the association between the kynurenine pathway and inflammation, we found a strong relation between these inflammatory markers and parameters for TRP oxidation [27,28,36]. The correlation between the KYN/TRP ratio and the NLR, which is an index of systemic inflammatory response [37], additionally strengthens this association.…”
Section: Discussionsupporting
confidence: 88%
“…Relevant changes in TRP metabolism are known to occur in neurodegenerative disorders and psychiatric conditions, but also in malignancy, end-stage renal failure, inflammatory disease, epilepsy and trauma [2][3][4][5][6][7][8][9][10][27][28][29][30]. The involvement of the kynurenine pathway in acute ischemic stroke is under current investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cancer patients, higher concentrations of serum neopterin, which is produced in large amounts by human monocytes/macrophages upon stimulation by IFN-␄, were reported, and measurement of serum neopterin allows assessment of the endogenous production of IFN-␄ [11,12,19,21]. Fuchs et al reported a significant positive correlation between neopterin concentration and Kyn/Trp ratio in serum of patients with several cancers, suggesting that increased IFN-␄ production in cancer patients is responsible for higher IDO activity, in particular, in macrophages and DC [11,12,19,21]. However, in the present study no association was found between the serum concentrations of IFN-␄ and the IDO activity in patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that modulated MPO levels and/or the acceleration of the rate of Trp degradation correlate with the extent of disease and predicting disease progression [3][4][5][6][7][8][9]. For example, cancer patients have enhanced degradation of Trp are not only found to predict shorter lifespan but are also associated with impaired quality of life [10][11][12]. In obesity, plasma tryptophan concentrations have been shown to be decreased and to be independent of weight reduction or dietary intake [13][14].…”
Section: Introductionmentioning
confidence: 99%